Social Sustainability of Palm Oil Industry: A Review - Ngan, Sue Lin; Er, Ah Choy; Yatim, Puan; How, Bing Shen; Lim, Chun Hsion; Ng, Wendy Pei Qin; Chan, Yi Herng; Lam, Hon Loong (Frontiers in Sustainability, 2022)
Climate change, resource scarcity, aging population are the most concerning global issue in recent decades. One of the best methods to manage and mitigate these problems while continuing to boost the economies and offer opportunities for the growing world population is sustainable development. As Malaysia is one of the major oil consumers in the world, the sustainability of palm oil has been controversial. Several sustainability standards are introduced to ensure the balance performance in terms of economic, environmental, and social performance of the industry. Nonetheless, the social aspect of the sustainability of palm oil has received relatively less emphasis as compared with the economic and environmental aspects. Literature, experts, and anecdotal evidence often claimed that it is due to the complication in assessing and evaluating social factors and impacts. Thus, this work aims to fill the gap in the literature on social sustainability for the palm oil industry both in terms of methods and facets. Suggested facets and its implication can enrich the theoretical contribution of this field while providing a comprehensive profile of the social sustainability of the palm oil industry. The outcomes also can be adopted by the policymakers and industry stakeholders to assess, manage, and enhance the social sustainability of the industry.